Preparation process of graphite nylon gasket for household appliances
Through oxidation, coupling and polymerization, and combining nylon and antioxidants, the uneven dispersion problem of graphite and nylon mixing is solved, and the mechanical properties and service life of graphite nylon washer is significantly improved, and the stability of graphite nylon washer is achieved. performance and performance improvement.
Patent Information
- Application Number
- CN202411451944.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The problem of poor service life caused by uneven dispersion when mixing graphite and nylon materials, the existing technology is difficult to effectively solve the uneven dispersion phenomenon caused by graphite agglomeration, which affects the performance and life of graphite nylon washer.
By oxidizing, coupling and polymerizing graphite, polyacrylate-graphite composite materials are prepared and blended with nylon and antioxidants. The plasma oxidation and ultrasonic dispersion technology are used to combine the modification of silane coupling agents to achieve Good dispersion of graphite forms a polyacrylate-graphite composite material.
It significantly improves the mechanical properties and service life of graphite nylon washer, solves the performance degradation caused by uneven dispersion, and improves the stability and processing performance of the material.
Smart Images

Figure BDA0005089392750000151 
Figure BDA0005089392750000161
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer sealing materials, and in particular relates to a preparation process of a graphite nylon gasket for household appliances. Background Art
[0002] A gasket is a ring-shaped material placed between two contact surfaces. As an important mechanical component, gaskets are widely used in various machines and equipment, mainly for sealing, supporting and preventing loosening. They play a vital role in modern engineering and manufacturing. With the advancement of science and technology and the development of materials science, the design, material selection and application fields of gaskets are constantly expanding, prompting their continuous improvement in performance and function. According to different functions and materials, gaskets can be divided into many types, including but not limited to the following categories: (1) Sealing gaskets: used to prevent fluid or gas leakage, commonly used in pipe connections, valves, flanges and other parts; (2) Flat washers: used as gaskets in mechanical connections, mainly used to disperse loads and prevent wear; (3) Spring washers: elastic, can automatically adapt to changes in the connection parts, and are often used to prevent loosening; (4) Rubber washers: using the elasticity and sealing properties of rubber, widely used in the sealing of liquids and gases. The material selection of gaskets directly affects their performance and service life. Common gasket materials include: (1) Metal materials: such as stainless steel, aluminum alloy, etc., which have good strength and high temperature resistance and are suitable for high pressure and high temperature environments; (2) Non-metallic materials: such as rubber, polytetrafluoroethylene (PTFE), polyurethane, etc., which have excellent sealing performance and chemical stability and are suitable for sealing various media; (3) Composite materials: Combining metal and non-metallic materials, aiming to take into account both strength and sealing, and are suitable for harsh environments.
[0003] With the advancement of technology, the design and manufacturing of gaskets are also constantly innovating. The development, research and expansion of high-performance materials have made it possible to improve the performance of gaskets, such as graphite and nylon materials. Graphite is a transitional crystal between atomic crystals, metal crystals and molecular crystals. Each carbon atom in the crystal is connected to three other carbon atoms. Six carbon atoms form a regular hexagonal ring on the same plane and stretch to form a lamellar structure. As an important industrial material, graphite has many excellent physical and chemical properties. First, graphite has good thermal conductivity and electrical conductivity, which makes it widely used in electrical and thermal management fields. Secondly, the high temperature resistance of graphite enables it to work stably in high temperature environments. In addition, the lubricating properties of graphite make it excellent in friction and wear, and it is suitable for use as a shock-absorbing and sealing material. In the home appliance industry, graphite is often used to make seals, lubricants and thermal conductive materials. For example, in the compressor of a refrigerator, graphite gaskets can effectively prevent refrigerant leakage and ensure the efficient operation of the equipment. In washing machines, the lubricating properties of graphite can reduce friction and improve the working efficiency and service life of the motor. Nylon, also known as polyamide, is a thermoplastic engineering plastic containing many repeated amide groups on the main chain of the molecule. Nylon is widely used in engineering plastics and has excellent mechanical properties and chemical resistance. The strength and toughness of nylon make it not easy to break when subjected to high loads and impacts. At the same time, the wear resistance of nylon makes it widely used in friction parts. In addition, nylon also has good water resistance and oil resistance, suitable for use in various environments. In the field of home appliances, nylon is often used to manufacture key components such as gears, bearings, and seals. These components need to withstand greater pressure and friction during work, so choosing the right material is crucial.
[0004] Composite graphite and nylon can give full play to the advantages of both, thus achieving better performance. First, the lubrication properties of graphite combined with the wear resistance of nylon make graphite nylon gaskets excellent in friction and wear, which can effectively extend the service life of the equipment. Secondly, the thermal conductivity of graphite combined with the insulation properties of nylon enables the composite material to maintain stable performance in high temperature environments. In addition, the chemical corrosion resistance of graphite combined with the water resistance of nylon allows graphite nylon gaskets to maintain good sealing performance in various harsh environments.
[0005] However, due to the large differences in the physical and chemical properties between nylon and graphite, the compatibility issues during the processing may make the performance of the new material obtained by combining the two unsatisfactory, and sometimes even lower than the performance of a single material. For this reason, people have started to study the mixing of the two materials.
[0006] Patent CN103937236A discloses a high-temperature resistant graphite nylon gasket material and a preparation method thereof. The invention uses nylon 66, graphite, polytetrafluoroethylene, diamine, maleic anhydride grafted polyphenylene ether, carbon fiber, aluminum bronze powder, paraben, flame retardant red phosphorus, activator, coupling agent, decabromodiphenyl ethane and heat-resistant anti-aging agent as raw materials, and obtains the high-temperature resistant graphite nylon gasket material by simple mixing, heating and stirring.
[0007] Patent CN103951972A discloses a corrosion-resistant graphite nylon gasket material. The invention uses nylon 6, graphite oxide, polyvinyl chloride, polyphenylene ether, maleic anhydride grafted polypropylene, glass fiber, n-decyl alcohol, silane coupling agent KH550, activator, lubricant and antioxidant as raw materials, nylon 6 as the main raw material, graphite oxide as filler, and other auxiliary components to improve the corrosion resistance and other properties of the graphite nylon gasket.
[0008] The main method of the above invention is to achieve the mixing of nylon material and graphite material by adding additional auxiliary components, so as to prepare graphite nylon gaskets with different properties. However, since graphite particles are easy to aggregate into agglomerates, they are unevenly dispersed when mixed with nylon materials. Although the tensile strength of the graphite nylon gasket can be temporarily improved by simply adding other auxiliary raw materials and simply mixing, it is difficult to solve the uneven dispersion phenomenon caused by agglomeration when graphite and nylon are mixed. As the use time increases, the uneven dispersion phenomenon has a non-negligible adverse effect on the service life of the graphite nylon gasket.
[0009] Therefore, how to solve the technical problem of poor service life of graphite nylon gaskets caused by uneven dispersion when graphite and nylon are mixed is of great significance for further improving the scope of use and economic value of graphite nylon gaskets. Summary of the invention
[0010] In view of the shortcomings of the prior art, the present invention obtains a polyacrylate-graphite composite material by oxidizing, coupling and polymerizing graphite in sequence, and then heat-blending with nylon, a plasticizer and an antioxidant to obtain a graphite nylon gasket, thereby solving the technical problems raised in the background technology. Specifically, the technical solution of the present invention includes the following contents:
[0011] A preparation process of a graphite nylon gasket for household appliances, the preparation process comprising the following steps:
[0012] The polymethyl acrylate-graphite composite material, nylon, plasticizer and antioxidant are put into an extruder according to a weight ratio of 8-21:46-73:3-4:0.6-1.1, and mixed at a speed of 100r / min-120r / min for 8min-12min in a temperature environment of 170°C-190°C to obtain the graphite nylon gasket.
[0013] Furthermore, the preparation method of the polymethyl acrylate-graphite composite material comprises the following steps:
[0014] Putting graphite into a plasma device for plasma oxidation treatment to obtain hydroxylated graphite;
[0015] A silane coupling agent, an organic solvent and water are mixed and heated to 40° C. to 50° C. for hydrolysis for 2 h to 3 h to obtain a silane coupling agent hydrolyzate, the hydroxylated graphite is first ultrasonically dispersed in the silane coupling agent hydrolyzate to form a dispersion, and the dispersion is heated and stirred to react to obtain silane coupling agent modified graphite;
[0016] The silane coupling agent modified graphite is ultrasonically dispersed in methyl acrylate for the second time, and then a free radical initiator is added, mixed and heated to 70-80° C. for reaction for 2h-4h to obtain the polymethyl acrylate-graphite composite material.
[0017] Furthermore, the conditions of the plasma oxidation treatment include an oxygen flow rate of 1 L / min to 1.5 L / min, a treatment power of 200 W to 250 W, and a treatment time of 3 min to 4 min.
[0018] Furthermore, the silane coupling agent includes vinyl trimethoxysilane, vinyl triethoxysilane or methyl vinyl dimethoxysilane, and the silane coupling agent needs to contain a carbon-carbon double bond structure in structure to facilitate subsequent polymerization.
[0019] Furthermore, the organic solvent includes ethanol, acetone or dimethyl sulfoxide.
[0020] Furthermore, the mass ratio of the silane coupling agent: the organic solvent: the water is 1:80-100:2-5.
[0021] Furthermore, the mass ratio of the hydroxylated graphite to the silane coupling agent is 4 to 6:1.
[0022] Furthermore, the conditions of the first ultrasonic dispersion include ultrasonic power of 100W to 200W and ultrasonic time of 20min to 30min.
[0023] Furthermore, the conditions for the dispersion heating and stirring reaction include a reaction temperature of 60° C. to 70° C., a rotation speed of 200 r / min to 400 r / min, and a reaction time of 1 h to 2 h.
[0024] Furthermore, the conditions of the second ultrasonic dispersion include ultrasonic power of 100W to 200W and ultrasonic time of 10min to 15min.
[0025] Furthermore, the free radical initiator includes potassium persulfate or ammonium persulfate.
[0026] Furthermore, the mass ratio of the silane coupling agent modified graphite: the methyl acrylate: the free radical initiator is 1:10-15:0.05-0.1.
[0027] Furthermore, the nylon includes nylon 6 or nylon 66, the plasticizer includes diethyl phthalate, dibutyl phthalate or triethyl citrate, and the antioxidant includes 2,6-di-tert-butyl-p-cresol, propyl gallate or tert-butylhydroquinone.
[0028] A graphite nylon gasket for household appliances is prepared by a preparation process of the graphite nylon gasket.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] In order to improve the technical problem that the graphite agglomeration causes uneven dispersion and thus leads to poor service life of the graphite nylon gasket, the present invention first uses plasma oxidation to oxidize the graphite surface to obtain hydroxylated graphite with reactive functional groups hydroxyl. The hydroxylated graphite is dispersed by means of the oscillating dispersion effect of ultrasound, but if it is not further treated after the ultrasonic treatment, the hydroxylated graphite molecules will re-aggregate due to the presence of intermolecular forces such as hydrogen bonding forces. The silane coupling agent with a carbon-carbon double bond functional group is pre-hydrolyzed to obtain a silane coupling agent hydrolyzate with a silanol functional group. Through the condensation between the silanol and the hydroxyl on the hydroxylated graphite, the silane coupling agent is introduced into the hydroxylated graphite surface to obtain silane coupling agent modified graphite. The introduction of the silane coupling agent reduces the mutual attraction between the hydroxylated graphites and prevents the aggregation between the hydroxylated graphites. Then, the carbon-carbon double bond on the silane coupling agent is polymerized with methyl acrylate to obtain a polymethyl acrylate-graphite composite material, and the silane coupling agent-modified graphite is further dispersed on the polymethyl acrylate molecules, which is not only beneficial to the dispersion of the silane coupling agent-modified graphite, but also utilizes the advantages of polymethyl acrylate such as good processing performance, good mechanical strength and biocompatibility, etc., which are easy to thermoplastically mold. Through the synergistic cooperation between the silane coupling agent-modified graphite, polymethyl acrylate and nylon, not only the problem of directly mixing graphite causing agglomeration due to uneven dispersion and thus resulting in poor service life of the graphite nylon gasket is solved, but also a positive effect is brought on the mechanical properties of the graphite nylon gasket. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0032] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.
[0033] Preparation Example 1:
[0034] The preparation method of polymethyl acrylate-graphite composite material specifically comprises the following steps:
[0035] Graphite particles were placed in the reaction chamber of the plasma equipment, the distance between the graphite particles and the plasma gas source was controlled to be 25 mm, and then the reaction chamber was evacuated using a vacuum pump, and oxygen was introduced at a flow rate of 1 L / min. At a power of 200 W, an oxidation treatment was performed for 3 minutes. After the treatment was completed, the plasma source was turned off, and the oxygen flow rate was gradually reduced until the oxygen supply was stopped. After the reaction chamber returned to normal pressure, the hydroxylated graphite was taken out.
[0036] 800g of ethanol and 20g of deionized water were mixed and added to a flask, and then 10g of vinyl trimethoxysilane was added and mixed and stirred evenly, and then heated to 40°C and the hydrolysis reaction was timed for 2h. After the hydrolysis was completed, 40g of hydroxylated graphite was added to the vinyl trimethoxysilane hydrolyzate, and then dispersed at an ultrasonic power of 100W for 20min. After the ultrasonic treatment was completed, it was immediately placed in an environment of 60°C and heated and stirred at a speed of 200r / min for 1h. After the reaction was completed, the solid was filtered and collected, and the solid was washed two to three times with anhydrous ethanol, and then dried to obtain vinyl trimethoxysilane modified graphite.
[0037] Weigh 20g of vinyl trimethoxysilane modified graphite and add it to 200g of methyl acrylate solution, and disperse it for 10min under 100W ultrasonic power. After the vinyl trimethoxysilane modified graphite is completely dispersed, add 1g of potassium persulfate and mix it, heat it to 70℃ and react for 2h. After the reaction is completed, dry it to obtain a polyacrylate-graphite composite material.
[0038] Preparation Example 2:
[0039] The preparation method of polymethyl acrylate-graphite composite material specifically comprises the following steps:
[0040] Graphite particles were placed in the reaction chamber of the plasma equipment, the distance between the graphite particles and the plasma gas source was controlled to be 26 mm, and then the reaction chamber was evacuated using a vacuum pump, and oxygen was introduced at a flow rate of 1.1 L / min. At a power of 210 W, the particles were subjected to oxidation treatment for 3 minutes. After the treatment was completed, the plasma source was turned off, and the oxygen flow rate was gradually reduced until the oxygen supply was stopped. After the reaction chamber returned to normal pressure, the hydroxylated graphite was taken out.
[0041] 850g of ethanol and 20g of deionized water were mixed and added to a flask, and then 10g of vinyl trimethoxysilane was added and mixed and stirred evenly, and then heated to 42°C and the hydrolysis reaction was timed for 2h. After the hydrolysis was completed, 45g of hydroxylated graphite was added to the vinyl trimethoxysilane hydrolyzate, and then dispersed at an ultrasonic power of 120W for 22min. After the ultrasonic treatment was completed, it was immediately placed in an environment of 60°C and heated and stirred at a speed of 250r / min for 1h. After the reaction was completed, the solid was filtered and collected, and the solid was washed two to three times with anhydrous ethanol, and then dried to obtain vinyl trimethoxysilane modified graphite.
[0042] Weigh 20g of vinyl trimethoxysilane modified graphite and add it to 220g of methyl acrylate solution, and disperse it for 11min at an ultrasonic power of 110W. After the vinyl trimethoxysilane modified graphite is completely dispersed, add 1.2g of potassium persulfate and mix it, heat it to 72℃, and react for 2h. After the reaction is completed, dry it to obtain a polyacrylate-graphite composite material.
[0043] Preparation Example 3:
[0044] The preparation method of polymethyl acrylate-graphite composite material specifically comprises the following steps:
[0045] Graphite particles were placed in the reaction chamber of the plasma equipment, the distance between the graphite particles and the plasma gas source was controlled at 27 mm, and then the reaction chamber was evacuated using a vacuum pump, and oxygen was introduced at a flow rate of 1.2 L / min. At a power of 220 W, an oxidation treatment was performed for 3 minutes. After the treatment was completed, the plasma source was turned off, and the oxygen flow rate was gradually reduced until the oxygen supply was stopped. After the reaction chamber returned to normal pressure, the hydroxylated graphite was taken out.
[0046] 850g of acetone and 30g of deionized water were mixed and added to a flask, and then 10g of vinyl triethoxysilane was added and mixed and stirred evenly, and then heated to 44°C and the hydrolysis reaction was timed for 2.5h. After the hydrolysis was completed, 45g of hydroxylated graphite was added to the vinyl triethoxysilane hydrolyzate, and then dispersed at an ultrasonic power of 140W for 24min. After the ultrasonic treatment was completed, it was immediately placed in an environment of 65°C and heated and stirred at a speed of 300r / min for 1.5h. After the reaction was completed, the solid was filtered and collected, and the solid was washed two to three times with anhydrous ethanol, and then dried to obtain vinyl triethoxysilane modified graphite.
[0047] Weigh 20g of vinyl triethoxysilane modified graphite and add it to 240g of methyl acrylate solution, and disperse it for 12min at 120W ultrasonic power. After the vinyl triethoxysilane modified graphite is completely dispersed, add 1.4g of potassium persulfate and mix it, heat it to 74℃ and react for 2.5h. After the reaction is completed, dry it to obtain a polyacrylate-graphite composite material.
[0048] Preparation Example 4:
[0049] The preparation method of polymethyl acrylate-graphite composite material specifically comprises the following steps:
[0050] Graphite particles were placed in the reaction chamber of the plasma equipment, the distance between the graphite particles and the plasma gas source was controlled to be 28 mm, and then the reaction chamber was evacuated using a vacuum pump, and oxygen was introduced at a flow rate of 1.3 L / min. At a power of 230 W, an oxidation treatment was performed for 4 minutes. After the treatment was completed, the plasma source was turned off, and the oxygen flow rate was gradually reduced until the oxygen supply was stopped. After the reaction chamber returned to normal pressure, the hydroxylated graphite was taken out.
[0051] 900g of acetone and 40g of deionized water were mixed and added to a flask, and then 10g of vinyl triethoxysilane was added and mixed and stirred evenly, and then heated to 46°C and the hydrolysis reaction was timed for 2.5h. After the hydrolysis was completed, 50g of hydroxylated graphite was added to the vinyl triethoxysilane hydrolyzate, and then dispersed at an ultrasonic power of 160W for 26min. After the ultrasonic treatment was completed, it was immediately placed in an environment of 65°C and heated and stirred at a speed of 350r / min for 1.5h. After the reaction was completed, the solid was filtered and collected, and the solid was washed two to three times with anhydrous ethanol, and then dried to obtain vinyl triethoxysilane modified graphite.
[0052] Weigh 20g of vinyl triethoxysilane modified graphite and add it to 260g of methyl acrylate solution, and disperse it for 13min at an ultrasonic power of 130W. After the vinyl triethoxysilane modified graphite is completely dispersed, add 1.6g of ammonium persulfate and mix it, heat it to 76℃ and react for 3h. After the reaction is completed, dry it to obtain a polyacrylate-graphite composite material.
[0053] Preparation Example 5:
[0054] The preparation method of polymethyl acrylate-graphite composite material specifically comprises the following steps:
[0055] Graphite particles were placed in the reaction chamber of the plasma equipment, the distance between the graphite particles and the plasma gas source was controlled at 29 mm, and then the reaction chamber was evacuated using a vacuum pump, and oxygen was introduced at a flow rate of 1.4 L / min. At a power of 240 W, an oxidation treatment was performed for 4 minutes. After the treatment was completed, the plasma source was turned off, and the oxygen flow rate was gradually reduced until the oxygen supply was stopped. After the reaction chamber returned to normal pressure, the hydroxylated graphite was taken out.
[0056] 950g of dimethyl sulfoxide and 40g of deionized water were mixed and added to a flask, and then 10g of methylvinyldimethoxysilane was added and mixed and stirred evenly, and then heated to 48°C and the hydrolysis reaction was timed for 3h. After the hydrolysis was completed, 55g of hydroxylated graphite was added to the methylvinyldimethoxysilane hydrolyzate, and then dispersed at an ultrasonic power of 180W for 28min. After the ultrasonic treatment was completed, it was immediately placed in a 70°C environment and heated and stirred at a speed of 350r / min for 1.5h. After the reaction was completed, the solid was filtered and collected, and the solid was washed two to three times with anhydrous ethanol, and then dried to obtain methylvinyldimethoxysilane-modified graphite.
[0057] Weigh 20g of methylvinyldimethoxysilane modified graphite and add it to 280g of methyl acrylate solution, and disperse it for 14min at an ultrasonic power of 140W. After the methylvinyldimethoxysilane modified graphite is completely dispersed, add 1.8g of ammonium persulfate and mix it, heat it to 78℃, and react for 3.5h. After the reaction is completed, dry it to obtain a polyacrylate-graphite composite material.
[0058] Preparation Example 6:
[0059] The preparation method of polymethyl acrylate-graphite composite material specifically comprises the following steps:
[0060] Graphite particles were placed in the reaction chamber of the plasma equipment, the distance between the graphite particles and the plasma gas source was controlled to be 30 mm, and then the reaction chamber was evacuated using a vacuum pump, and oxygen was introduced at a flow rate of 1.5 L / min. At a power of 250 W, an oxidation treatment was performed for 4 minutes. After the treatment was completed, the plasma source was turned off, and the oxygen flow rate was gradually reduced until the oxygen supply was stopped. After the reaction chamber returned to normal pressure, the hydroxylated graphite was taken out.
[0061] 1000g of dimethyl sulfoxide and 50g of deionized water were mixed and added to a flask, and then 10g of methylvinyldimethoxysilane was added and mixed and stirred evenly, and then heated to 50°C and the hydrolysis reaction was timed for 3h. After the hydrolysis was completed, 60g of hydroxylated graphite was added to the methylvinyldimethoxysilane hydrolyzate, and then dispersed for 30min at an ultrasonic power of 200W. After the ultrasonic treatment was completed, it was immediately placed in an environment of 70°C and heated and stirred at a speed of 400r / min for 2h. After the reaction was completed, the solid was filtered and collected, and the solid was washed two to three times with anhydrous ethanol, and then dried to obtain methylvinyldimethoxysilane-modified graphite.
[0062] Weigh 20g of methylvinyldimethoxysilane modified graphite and add it to 300g of methyl acrylate solution, and disperse it for 15min under 150W ultrasonic power. After the methylvinyldimethoxysilane modified graphite is completely dispersed, add 2g of ammonium persulfate and mix it, heat it to 80℃ and react for 4h. After the reaction is completed, dry it to obtain a polyacrylate-graphite composite material.
[0063] Preparation Example 7:
[0064] The preparation method of hydroxylated graphite specifically comprises the following steps:
[0065] Graphite particles were placed in the reaction chamber of the plasma equipment, the distance between the graphite particles and the plasma gas source was controlled to be 30 mm, and then the reaction chamber was evacuated using a vacuum pump, and oxygen was introduced at a flow rate of 1.5 L / min. At a power of 250 W, an oxidation treatment was performed for 4 minutes. After the treatment was completed, the plasma source was turned off, and the oxygen flow rate was gradually reduced until the oxygen supply was stopped. After the reaction chamber returned to normal pressure, the hydroxylated graphite was taken out.
[0066] Preparation Example 8:
[0067] The preparation method of methylvinyldimethoxysilane modified graphite specifically comprises the following steps:
[0068] Graphite particles were placed in the reaction chamber of the plasma equipment, the distance between the graphite particles and the plasma gas source was controlled to be 30 mm, and then the reaction chamber was evacuated using a vacuum pump, and oxygen was introduced at a flow rate of 1.5 L / min. At a power of 250 W, an oxidation treatment was performed for 4 minutes. After the treatment was completed, the plasma source was turned off, and the oxygen flow rate was gradually reduced until the oxygen supply was stopped. After the reaction chamber returned to normal pressure, the hydroxylated graphite was taken out.
[0069] 1000g of dimethyl sulfoxide and 50g of deionized water were mixed and added to a flask, and then 10g of methylvinyldimethoxysilane was added and mixed and stirred evenly, and then heated to 50°C and the hydrolysis reaction was timed for 3h. After the hydrolysis was completed, 60g of hydroxylated graphite was added to the methylvinyldimethoxysilane hydrolyzate, and then dispersed for 30min at an ultrasonic power of 200W. After the ultrasonic treatment was completed, it was immediately placed in an environment of 70°C and heated and stirred at a speed of 400r / min for 2h. After the reaction was completed, the solid was filtered and collected, and the solid was washed two to three times with anhydrous ethanol, and then dried to obtain methylvinyldimethoxysilane-modified graphite.
[0070] Preparation Example 9:
[0071] The preparation method of the polytetrafluoroethylene-graphite composite material specifically comprises the following steps:
[0072] Tetrafluoroethylene gas was introduced into a high-pressure reactor, and 20 times the amount of tetrafluoroethylene of water and 0.05 times the amount of tetrafluoroethylene of the surfactant sodium dodecylbenzene sulfonate were added and mixed. Then 0.1 times the amount of tetrafluoroethylene of the vinyldimethoxysilane modified graphite obtained in Preparation Example 6 was added into the reactor, and then 0.008 times the amount of tetrafluoroethylene of ammonium persulfate was added. The pressure was controlled at 4±1MPa and the temperature was 65±5°C, and the polymerization reaction was carried out for 5 hours to obtain a polytetrafluoroethylene-graphite composite material.
[0073] Preparation Example 10:
[0074] The preparation method of polymethyl acrylate-graphite composite material specifically comprises the following steps:
[0075] The methylvinyldimethoxysilane in Preparation Example 6 was replaced by γ-glycidyloxypropyltrimethoxysilane, and the other conditions were kept consistent with Preparation Example 6.
[0076] Embodiment 1:
[0077] A preparation process of graphite nylon gasket for household appliances, specifically comprising the following processes:
[0078] 8 parts by weight of the polyacrylate-graphite composite material of Preparation Example 1, 46 parts by weight of nylon 6, 3 parts by weight of diethyl phthalate and 0.6 parts by weight of 2,6-di-tert-butyl-p-cresol were weighed and put into an extruder, the temperature of the extruder was controlled to be 170° C., and then the mixture was blended at a speed of 100 r / min for 8 minutes. After the blending was completed, the mixture was poured into a mold to obtain a graphite nylon gasket.
[0079] Embodiment 2:
[0080] A preparation process of graphite nylon gasket for household appliances, specifically comprising the following processes:
[0081] 10 parts by weight of the polyacrylate-graphite composite material of Preparation Example 2, 50 parts by weight of nylon 6, 3.2 parts by weight of diethyl phthalate and 0.7 parts by weight of 2,6-di-tert-butyl-p-cresol were weighed and put into an extruder, the temperature of the extruder was controlled to be 175° C., and then the blending time was 8 minutes at a speed of 100 r / min. After the blending was completed, it was poured into a mold to obtain a graphite nylon gasket.
[0082] Embodiment 3:
[0083] A preparation process of graphite nylon gasket for household appliances, specifically comprising the following processes:
[0084] 13 parts by weight of the polyacrylate-graphite composite material of Preparation Example 3, 55 parts by weight of nylon 6, 3.4 parts by weight of dibutyl phthalate and 0.8 parts by weight of propyl gallate were weighed and put into an extruder, the temperature of the extruder was controlled to be 180° C., and then the blending time was 10 minutes at a speed of 110 r / min. After the blending was completed, it was poured into a mold to obtain a graphite nylon gasket.
[0085] Embodiment 4:
[0086] A preparation process of graphite nylon gasket for household appliances, specifically comprising the following processes:
[0087] 16 parts by weight of the polyacrylate-graphite composite material of Preparation Example 4, 62 parts by weight of nylon 66, 3.6 parts by weight of dibutyl phthalate and 0.9 parts by weight of propyl gallate were weighed and put into an extruder, the temperature of the extruder was controlled to be 180° C., and then the blending time was 10 minutes at a speed of 110 r / min. After the blending was completed, it was poured into a mold to obtain a graphite nylon gasket.
[0088] Embodiment 5:
[0089] A preparation process of graphite nylon gasket for household appliances, specifically comprising the following processes:
[0090] 20 parts by weight of the polyacrylate-graphite composite material of Preparation Example 5, 70 parts by weight of nylon 66, 3.8 parts by weight of triethyl citrate and 1 part by weight of tert-butylhydroquinone were weighed and put into an extruder, the temperature of the extruder was controlled to be 185° C., and then the mixture was blended at a speed of 120 r / min for 12 minutes. After the blending was completed, the mixture was poured into a mold to obtain a graphite nylon gasket.
[0091] Embodiment 6:
[0092] A preparation process of graphite nylon gasket for household appliances, specifically comprising the following processes:
[0093] 21 parts by weight of the polyacrylate-graphite composite material of Preparation Example 6, 73 parts by weight of nylon 66, 4 parts by weight of triethyl citrate and 1.1 parts by weight of tert-butylhydroquinone were weighed and put into an extruder, the temperature of the extruder was controlled to be 190° C., and then the mixture was blended at a speed of 120 r / min for 12 minutes. After the blending was completed, the mixture was poured into a mold to obtain a graphite nylon gasket.
[0094] Comparative Example 1:
[0095] A preparation process of graphite nylon gasket for household appliances, specifically comprising the following processes:
[0096] 21 parts by weight of the polyacrylate-graphite composite material of Preparation Example 7, 73 parts by weight of nylon 66, 4 parts by weight of triethyl citrate and 1.1 parts by weight of tert-butylhydroquinone were weighed and put into an extruder, the temperature of the extruder was controlled to be 190° C., and then the mixture was blended at a speed of 120 r / min for 12 minutes. After the blending was completed, the mixture was poured into a mold to obtain a graphite nylon gasket.
[0097] Comparative Example 2:
[0098] A preparation process of graphite nylon gasket for household appliances, specifically comprising the following processes:
[0099] 21 parts by weight of the polyacrylate-graphite composite material of Preparation Example 8, 73 parts by weight of nylon 66, 4 parts by weight of triethyl citrate and 1.1 parts by weight of tert-butylhydroquinone were weighed and put into an extruder, the temperature of the extruder was controlled to be 190° C., and then the mixture was blended at a speed of 120 r / min for 12 minutes. After the blending was completed, the mixture was poured into a mold to obtain a graphite nylon gasket.
[0100] Comparative Example 3:
[0101] A preparation process of graphite nylon gasket for household appliances, specifically comprising the following processes:
[0102] 21 parts by weight of the polyacrylate-graphite composite material of Preparation Example 9, 73 parts by weight of nylon 66, 4 parts by weight of triethyl citrate and 1.1 parts by weight of tert-butylhydroquinone were weighed and put into an extruder, the temperature of the extruder was controlled to be 190° C., and then the mixture was blended at a speed of 120 r / min for 12 minutes. After the blending was completed, the mixture was poured into a mold to obtain a graphite nylon gasket.
[0103] Comparative Example 4:
[0104] 21 parts by weight of the polyacrylate-graphite composite material of Preparation Example 10, 73 parts by weight of nylon 66, 4 parts by weight of triethyl citrate and 1.1 parts by weight of tert-butylhydroquinone were weighed and put into an extruder, the temperature of the extruder was controlled to be 190° C., and then the mixture was blended at a speed of 120 r / min for 12 minutes. After the blending was completed, the mixture was poured into a mold to obtain a graphite nylon gasket.
[0105] Comparative Example 5:
[0106] A preparation process of graphite nylon gasket for household appliances, specifically comprising the following processes:
[0107] 21 parts by weight of unmodified graphite, 73 parts by weight of nylon 66, 4 parts by weight of triethyl citrate and 1.1 parts by weight of tert-butylhydroquinone were weighed and put into an extruder, the temperature of the extruder was controlled to be 190° C., and then the blending time was 12 minutes at a speed of 120 r / min. After the blending was completed, it was poured into a mold to obtain a graphite nylon gasket.
[0108] The graphite nylon washers and nylon 66 obtained in Examples 1 to 6 and Comparative Examples 1 to 5 were tested for tensile strength according to "Determination of tensile properties of plastics in GB / T 1040.2-2022", and then aged for 50 days in an environment of 50°C and 100°C, respectively, and then the tensile strength after aging was measured according to "Determination of tensile properties of plastics in GB / T 1040.2-2022". The results are shown in the following table:
[0109]
[0110]
[0111] From the above test data we can see that:
[0112] (1) The present invention achieves good dispersion of graphite by utilizing plasma oxidation treatment, modification of silane coupling agent and synergistic effect of polymethyl acrylate. This treatment method not only improves the mechanical properties of graphite nylon gaskets, but also improves the service life of graphite nylon gaskets.
[0113] (2) It can be seen from Comparative Example 1 that the mechanical properties and service life of the graphite nylon gasket finally prepared by only subjecting the graphite to plasma oxidation dispersion are poor. This may be because when the hydroxylated graphite loses ultrasonic dispersion and is subsequently mixed, the hydrogen bonding between the hydroxyl groups causes the hydroxylated graphite to re-aggregate, which is not conducive to dispersion.
[0114] (3) It can be seen from Comparative Example 2 that although the dispersion of hydroxylated graphite can be improved by using only a silane coupling agent, the dispersion effect is not strong, resulting in poor mechanical properties and service life of the prepared graphite nylon gasket.
[0115] (4) It can be seen from Comparative Example 3 that although tetrafluoroethylene can also achieve the same polymerization and dispersion effect as methyl acrylate, the thermoplasticity of the polytetrafluoroethylene obtained after polymerization is poor, which slightly reduces the mechanical properties and life of the prepared graphite nylon gasket.
[0116] (5) It can be seen from Comparative Example 4 that γ-glycidyloxypropyltrimethoxysilane does not have a carbon-carbon double bond reactive group and cannot connect graphite to polymethyl acrylate through a polymerization reaction. The dispersibility of polymethyl acrylate is not utilized, resulting in poor mechanical properties and life of the graphite nylon gasket.
[0117] (6) It can be seen from Comparative Example 5 that due to the agglomeration nature of graphite, simply blending cannot effectively improve the dispersion properties of graphite. Instead, it causes the mechanical properties of the prepared graphite nylon gasket to decrease. This may be due to the serious agglomeration of the untreated graphite, which leads to poor dispersion in the nylon material and is not conducive to material modification.
[0118] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.
Claims
1. A process for preparing graphite nylon gaskets for household appliances, characterized in that: The preparation process comprises the following steps: The polymethyl acrylate-graphite composite material, nylon, plasticizer and antioxidant are put into an extruder according to a weight ratio of 8-21:46-73:3-4:0.6-1.1, and mixed at a speed of 100r / min-120r / min for 8min-12min in a temperature environment of 170°C-190°C to obtain the graphite nylon gasket.
2. The preparation process of a graphite nylon gasket for household appliances according to claim 1, characterized in that: The preparation method of the polymethyl acrylate-graphite composite material comprises the following steps: Putting graphite into a plasma device for plasma oxidation treatment to obtain hydroxylated graphite; A silane coupling agent, an organic solvent and water are mixed and heated to 40° C. to 50° C. for hydrolysis for 2 h to 3 h to obtain a silane coupling agent hydrolyzate, the hydroxylated graphite is first ultrasonically dispersed in the silane coupling agent hydrolyzate to form a dispersion, and the dispersion is heated and stirred to react to obtain silane coupling agent modified graphite; The silane coupling agent modified graphite is ultrasonically dispersed in methyl acrylate for the second time, and then a free radical initiator is added, mixed and heated to 70-80° C. for reaction for 2h-4h to obtain the polymethyl acrylate-graphite composite material.
3. The preparation process of a graphite nylon gasket for household appliances according to claim 2, characterized in that: The conditions of the plasma oxidation treatment include an oxygen flow rate of 1 L / min to 1.5 L / min, a treatment power of 200 W to 250 W, and a treatment time of 3 min to 4 min.
4. The preparation process of a graphite nylon gasket for household appliances according to claim 2, characterized in that: The silane coupling agent includes vinyl trimethoxy silane, vinyl triethoxy silane or methyl vinyl dimethoxy silane.
5. The preparation process of a graphite nylon gasket for household appliances according to claim 2, characterized in that: The mass ratio of the silane coupling agent: the organic solvent: the water is 1:80-100:2-5.
6. The preparation process of a graphite nylon gasket for household appliances according to claim 2, characterized in that: The mass ratio of the hydroxylated graphite to the silane coupling agent is 4 to 6:
1.
7. The preparation process of a graphite nylon gasket for household appliances according to claim 2, characterized in that: The conditions for the heating and stirring reaction of the dispersion liquid include a reaction temperature of 60° C. to 70° C., a rotation speed of 200 r / min to 400 r / min, and a reaction time of 1 h to 2 h.
8. The process for preparing a graphite nylon gasket for household appliances according to claim 2, characterized in that: The mass ratio of the silane coupling agent modified graphite: the methyl acrylate: the free radical initiator is 1:10-15:0.05-0.
1.
9. The preparation process of a graphite nylon gasket for household appliances according to claim 1, characterized in that: The nylon includes nylon 6 or nylon 66, the plasticizer includes diethyl phthalate, dibutyl phthalate or triethyl citrate, and the antioxidant includes 2,6-di-tert-butyl-p-cresol, propyl gallate or tert-butylhydroquinone.
10. A graphite nylon gasket prepared by the process for preparing a graphite nylon gasket for household appliances according to any one of claims 1 to 9.
